Marine Phenolics Extraction and Purification, Identification, Characterization and Applications - Domínguez, Herminia; Pérez-Correa, José Ricardo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Phenolic compounds are an extremely diverse class of ubiquitous secondary metabolites produced by a variety of organisms playing different biological roles. They have numerous types of demonstrated bioactivities, including antioxidant, antimicrobial, anti-inflammatory, antitumoral, immunomodulator, neuroprotective, cardioprotective, and antidiabetic activities. Marine organisms produce a vast collection of unique phenolic structures, some of them not found in terrestrial habitats. Progress in different aspects is rapidly advancing, and this Special Issue will provide updated information and recent studies on marine phenolics. Specially, this issue is focused on their chemical characterization, elucidation of their structures, evaluation of their biological properties and mechanisms of action, efficient extraction and purification technologies, development of value-added applications, as well as formulation of novel products.